SURVEI TINGKAT KEBUGARAN JASMANI SISWA KELAS II IPA SMA NEGERI 2 BOARDING SCHOOL BANDA ACEH TAHUN AJARAN 2018/2019 - zikrur Zik Zikrur Rahmat (Universitas Syiah Kuala, 2022)
The purposes the studi aims to measure and determine the number of physical fitness is the ability of a person's body to carry out daily tasks and work without causing significant fatigue, so that the body still has energy reserves to overcome the burden of savings. Class II IPA SMA Negeri 2 Boarding School Banda Aceh 2018/2019 Academic Year. The method used in this study is descriptive quantitative method. The population of this research is the second grade science students of SMA Negeri 2 Boarding School Banda Aceh for the 2018/2019 academic year. While the sample represented was 40 students of class II SMA Negeri 2 Boarding School Banda Aceh using the Random Sampling technique using the Indonesian Physical Fitness Level (TKJI) test. The results of data processing show that the average level of physical fitness varies. So the overall picture of the Physical Fitness Level of Class II Science Students at SMA Negeri 2 Bording School Banda Aceh for the 2018/2019 Academic Year is that of 40 students (100%) there are 0 students (0%) in the very good category, 16 students (40%) in the category good, 21 students (52.5%) in the moderate category, 3 students (7.5%) and 0 students (0%) in the very poor category. The conclusion of this study can be concluded that the level of physical fitness of students II IPA SMA Negeri 2 Boarding School Banda Aceh City is moderate. The conclusion is that more than 40 students (100%) there are 0 students (0%) in the very good category, 16 students (40%) in the good category, 21 students (52.5%) in the medium category, 3 students (7 ,5%) and 0 students (0%) in the category of very less